2018
DOI: 10.1017/s1743923x18000673
|View full text |Cite
|
Sign up to set email alerts
|

Double Standards: The Role of Gender and Intraparty Politics in Swedish Cabinet Appointments

Abstract: Are female politicians less likely to be promoted to specific ministerial posts, and is it important for them to toe the party line? This article focuses on whether the selection of ministers has a gender-specific dimension. Building on role congruity theory and research showing that female and male politicians are evaluated in a different manner in leadership positions, we present some original hypotheses. For example, we hypothesize that female politicians are less likely to be appointed to cabinet when they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 50 publications
(88 reference statements)
1
14
0
4
Order By: Relevance
“…Analyzing thousands of parliamentary speeches in Turkey, Yildirim, Kocapnar, and Ecevit (2021) find that whereas men MPs who were active on the legislative floor were significantly more likely to get renominated and promoted in the party rank, women who were active in legislative speech making were less likely to be renominated and promoted. Similarly, research on ministerial selection in Sweden shows that women MPs who deviated from the party line during parliamentary speeches were less likely to be appointed to cabinet posts, whereas this pattern was not found among men (Baumann, Bäck, and Davidsson 2019). We expect a similar dynamic in our cases.…”
Section: Gendered Expectations Of Legislative Behaviorsupporting
confidence: 60%
See 1 more Smart Citation
“…Analyzing thousands of parliamentary speeches in Turkey, Yildirim, Kocapnar, and Ecevit (2021) find that whereas men MPs who were active on the legislative floor were significantly more likely to get renominated and promoted in the party rank, women who were active in legislative speech making were less likely to be renominated and promoted. Similarly, research on ministerial selection in Sweden shows that women MPs who deviated from the party line during parliamentary speeches were less likely to be appointed to cabinet posts, whereas this pattern was not found among men (Baumann, Bäck, and Davidsson 2019). We expect a similar dynamic in our cases.…”
Section: Gendered Expectations Of Legislative Behaviorsupporting
confidence: 60%
“…As such, members of the (s)electorate may be more likely to punish undisciplined behavior when it comes from women. While parties or voters might tolerate "maverick" men, undisciplined women may have less influence in their legislative work and may be less likely to be renominated, reelected, or promoted (Baumann, Bäck, and Davidsson 2019). In sum, assertive behavior, such as rebelling against the party line, may be a more effective legislative style among men than among women.…”
Section: Gendered Expectations Of Legislative Behaviormentioning
confidence: 99%
“…Although gendered patterns in the ministerial selection are changing, a similarly continued underrepresentation can also be uncovered in the distribution of minister portfolios (Escobar-Lemmon & Taylor-Robinson, 2005;Goddard, 2019;Krook & O'Brien, 2012), also in the specific context of Belgium (Dumont et al, 2008). Even though research shows how gender role incongruent behavior might negatively affect female MPs' career prospects (e.g., in terms of ministerial appointments; Baumann et al, 2019) which could lead to frustrations and more critical behavior towards male office-holders in hard domains, we hypothesize that female opposition MPs more often target female ministers compared to male MPs, due to generally persistent parallel patterns in parliamentary issue specialization and ministerial portfolio allocation, and female ministers being more responsive to the speeches of female MPs. H4: Female opposition MPs target female ministers more often compared to male opposition MPs.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…While the share of women in the executive branch of government has steadily increased over the last decades and the recent formation of 'parity cabinets' in Canada (Trudeau) and Spain (Sanchez) has attracted much attention in the media, this positive trend masks an important problem: The selection of women to cabinet positions is not gender neutral and, consequently, a higher number of female ministers does not reveal anything about the types of portfolios that women receive (Baumann et al, 2019;Goddard, 2019Goddard, , 2021. Previous research has, for example, shown that women are disproportionally relegated to less prestigious ministries as well as to portfolios responsible for 'soft' or 'feminine' policy areas like education, culture or women's affairs (Escobar-Lemmon and Taylor-Robinson, 2005;Krook and O'Brien, 2012;Kroeber and Hüffelmann, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas men are typically seen as dominant, controlling and are expected to be 'prone to act as a leader', women are stereotypically characterized as helpful, nurturing and sensitive (Eagly and Karau, 2002: 574). Therefore, role congruity theory predicts that women in leadership positions will be confronted with prejudice and hostility due to the dissimilarities between the typical expectations that people have about women and their ideal type of a leader (Baumann et al, 2019). Thus, parties are more likely to choose men than women as the 'appropriate' leaders of their most salient ministries and relegate women to those policy fields that are less important for the party.…”
Section: Introductionmentioning
confidence: 99%